Cholesterol modified DP7 and pantothenic acid induce dendritic cell homing to enhance the efficacy of dendritic cell vaccines - Rui Zhang (Springer, 2021)
Abstract Dendritic cell (DC)-based cancer vaccines have so far achieved good therapeutic effects in animal experiments and early clinical trials for certain malignant tumors. However, the overall objective response rate in clinical trials rarely exceeds 15%. The poor efficiency of DC migration to lymph nodes (LNs) (< 5%) is one of the main factors limiting the effectiveness of DC vaccines. Therefore, increasing the efficiency of DC migration is expected to further enhance the efficacy of DC vaccines. Here, we used DP7-C (cholesterol modified VQWRIRVAVIRK), which can promote DC migration, as a medium. Through multiomics sequencing and biological experiments, we found that it is the metabolite pantothenic acid (PA) that improves the migration and effectiveness of DC vaccines. We clarified that both DP7-C and PA regulate DC migration by regulating the chemokine receptor CXCR2 and inhibiting miR-142a-3p to affect the NF-κB signaling pathway. This study will lay the foundation for the subsequent use of DP7-C as a universal substance to promote DC migration, further enhance the antitumor effect of DC vaccines, and solve the bottleneck problem of the low migration efficiency and unsatisfactory clinical response rate of DC vaccines.